KONSEP PAYANGO PADA RUMAH TINGGAL TRADISIONAL DI GORONTALO - Umar; Emil Fatra; Thiara Tri Funny Manguma (KIRANA : Social Science Journal, 2024)
Gorontalo, a province located in the north of the island of Sulawesi, has a form of cultural custom regarding the procedures for making a building which has a very important meaning in development, called the concept of "payango". This research aims to find out how the payango concept is applied to traditional houses in Gorontalo.. The method used in this research is qualitative analysis using an ethnographic approach. The results of research on the Payango concept in Gorontalo people's houses regulate determining the basic size of the house (length and width), determining the placement of Pulo Payango (starting point), digging foundations or pillars, determining 5 points for placing Payango materials, determining the orientation/direction of the building, and determining the position of the doors and windows of the house